A CTML-Guided Virtual Reality Framework for Conceptual Learning in Islamic Civilization History - Deni Hardianto; M. Vithor Al Faqih; Maulana Afif Ramdhoni; June Onaritha Leky; Anggi Widiarni (Online Learning In Educational Research (OLER), 2026)
Developing meaningful conceptual understanding in history education requires more than immersive visualization; it demands instructional designs that effectively manage learners’ cognitive processes. However, most virtual reality (VR) applications in history education emphasize sensory immersion while providing limited cognitive guidance. This study developed and validated a CTML-guided virtual reality learning framework for teaching Islamic Civilization History to junior secondary students. Using the ADDIE research and development model, the VR environment was designed by integrating five principles of the Cognitive Theory of Multimedia Learning (CTML): pre-training, segmentation, signaling, modality, and coherence. The learning environment features four interconnected historical scenes, interactive three-dimensional objects, audio narration, informative hotspots, and generative microtasks that encourage active conceptual processing. Expert evaluation confirmed the framework’s high pedagogical and technical feasibility, while student trials demonstrated positive usability, engagement, and perceived learning value following iterative refinements. The findings suggest that integrating CTML principles into immersive environments can transform virtual reality from a technology-centered experience into a cognitively guided learning environment that supports conceptual understanding. This study contributes a practical instructional framework for designing theory-driven virtual reality learning environments in history and other conceptually demanding disciplines